Current guidelines in peritoneal dialysis - Part I - Ferreira,Ana Carina (2019)
A successful peritoneal dialysis program follows evidence-based practice guidelines. In this first article we review the current guidelines on catheter insertion and on prevention of catheter-related infections, both subjects of extreme importance not only to initiate and also to maintain patients on peritoneal dialysis. The treatment of catheter-related infections is not part of the purpose of this article.